Developing integration among stakeholders in the primary care networks of Singapore: a qualitative study - Shilpa Surendran; Chuan De Foo; David Bruce Matchar; John Pastor Ansah; Josip Car; Gerald Choon Huat Koh (BMC Health Services Research, 2022)
Abstract Background Integrating healthcare services across and between the different health system levels can be achieved in a few ways; however, examining the social side of integration is essential and challenging. This paper explores the concept of integration perceived by general practitioners (GPs) and primary care network (PCN) representatives from the regional health systems (RHS) in a GP-RHS PCN and their perceived partnership success. Methods In this study, we explored three GP-RHS PCNs in Singapore. We used a qualitative research design and, overall, performed 17 semi-structured in-depth interviews with GPs (n = 11) and PCN representatives (n = 6) from the RHS. All interviews were audiotaped and transcribed verbatim. We conducted thematic analysis to inductively identify themes from the data. Singer's conceptual model of integration types was used as guiding principles to derive relevant and salient themes for integration. Results GPs and the RHS perceived the concept of integration through a series of interrelated strategies. Within the normative dimension, a sense of urgency motivated GPs to integrate improvements into their general practice. Participants perceived teamwork and relational climate as appropriate enablers for achieving interpersonal integration in a primary care partnership. While developing a trusted relationship was a perceived success of this partnership across the network, developing camaraderie and gaining knowledge in chronic disease management through the components of functional integration was a perceived success at an individual general practice level. The data also revealed some operational challenges within the structural dimension and some inabilities of the PCN to achieve complete process integration. Conclusions Our study points to multi-faceted integration, comprising various forms that need to be manifested at all levels of care to achieve coordinated, seamless, and comprehensive care for patients suffering from chronic conditions. The present iteration of the PCN has been shown to offer integration at a level that warrants praise but still requires structural and process integration improvement.